Crisis Resource Management for Third-Year Medical Students: A Simulation Curriculum - Ilana Harwayne-Gidansky; Alexandra Leader; Sheemon Zackai; Christopher Strother (Association of American Medical Colleges, 2014)
Abstract Introduction Effective communication is critical to crisis situations. Crisis resource management (CRM) has been an established part of the anesthesiology curriculum for close to 20 years and in emergency departments for the better part of the decade. However, it has yet to find a place in pediatrics training. Pediatric crises occur less often than in other specialties and are different from adult crises, and they are uniquely stressful. Because of their rare occurrence, students and residents are often ill-prepared when they arise. In response to this, we designed a 90-minute simulation module to introduce third-year medical students to the principles of CRM on a high-fidelity simulator during their pediatric clerkship. Methods This module has been written with a focus on discussing improvements that could have been made during each simulation activity. A debriefing session directly follows each simulation activity at which time the observers provide feedback to the participating student. Included in this submission are a guide to the module, a synopsis of both respiratory-to-cardiac-arrest simulation cases, CRM lecture slides, a bag-valve-mask skills workshop, and a student evaluation. Results One hundred thirty-eight medical students participated in our module during their pediatric clerkship. A subjective assessment showed statistically significant improvement in attitudes and confidence of medical students immediately after participating in the simulation session. Specifically, students reported that they felt more comfortable in a pediatric resuscitation (p < .001, 35% change in those who agreed) after participating in this module. They also reported feeling better able to communicate well in a pediatric resuscitation (p < .001, 41% change in those who agreed) and better at understanding what their role was during a pediatric resuscitation (p < .001, 62% change in those who agreed). Discussion Although this module may be completed in a 60-minute time slot, we recommend at least 90 minutes if including the manual bag-valve mask skills component, in order to have time for a more thorough debriefing. We limited our evaluations to manual bag-valve mask skills and CRM skills. Similar modules may be used several times during a student's pediatric rotation in order to focus on additional manual and communication skills. In the future, we hope to implement a multi-institutional study using these materials as the basis of future research.